PEMBAGIAN HARTA BERSAMA PASCA PERCERAIAN BAGI ISTERI YANG BERKARIER (STUDI TERHADAP PUTUSAN PENGADILAN AGAMA BENGKULU) - Hak, Nurul; Marni, Meli Musli (UIN Fatmawati Sukarno Bengkulu, 2017)
Division of joint post-divorce property for a career wife (a study of the Bengkulu Religious Court’s decision). There are two problems in this research, namely, how the concept of sharing of joint property for the wife of a career in the event of divorce, and what is the basis of judges consideration of Bengkulu Religious Court in deciding the case of sharing of joint property for the wife of a career. Descriptive qualitative research method, while data collection techniques are documentation, observation and interview. Data sources include primary and secondary data. The informant of the judges of the Bengkulu Religious Court. Secondary data of religious court ruling on the distribution of common property. The results of this study explain that the distribution of joint property for wives whose career is not clearly regulated in the Compilation of Islamic Law, therefore in the case of sharing of joint property for the wife of a career, becomes the ijtihad area of the judge to see the case casuistically by taking into account the contribution and role of each. Respectively. The basis of consideration of the judges of the Bengkulu Religious Court in determining the distribution of joint property for wives of post-divorce careers, has been in accordance with theories based on the judges’ good judgment, procedurally in accordance with applicable law, because in its judgment the judge has taken legal norms Appropriate to the articles in the legislation, and has fulfilled the normative juridical aspects, sociological and philosophical, so that the realization of legal certainty, legal justice and legal benefits. Consideration of the judges of the Bengkulu Religious Court in deciding the case of sharing of joint property for the wife of the career, the majority of the decision based on the provisions of the Compilation of Islamic Law, some judges to explore other sources of law as required Article 5 paragraph (1) Law Number 48 Year 2009 on Judicial Power And the principle of ius novita novit, in deciding the matter of sharing the property with the judges of the Bengkulu Religious Court based on casuistry.